Polygonatum cyrtonema polysaccharides reshape the gut microbiota to ameliorate dextran sodium sulfate-induced ulcerative colitis in mice - Lin, Chaoyou; Song, Dawei; Wang, Shangwen; Chu, Yunfei; Chi, Changxing; Jia, Sining; Lin, Mengyi; He, Chenbei; Jiang, Chengxi; Gong, Fanghua; Chen, Qiongzhen (Frontiers in Pharmacology, 2024)
Ulcerative colitis (UC) is a chronic inflammatory bowel disease characterized inflammatory imbalance, intestinal epithelial mucosal damage, and dysbiosis of the gut microbiota. Polygonatum cyrtonema polysaccharides (PCPs) can regulate gut microbiota and inflammation. Here, the different doses of PCPs were administered to dextran sodium sulfate-induced UC mice, and the effects of the whole PCPs were compared with those of the fractionated fractions PCP-1 (19.9 kDa) and PCP-2 (71.6 and 4.2 kDa). Additionally, an antibiotic cocktail was administered to UC mice to deplete the gut microbiota, and PCPs were subsequently administered to elucidate the potential role of the gut microbiota in these mice. The results revealed that PCP treatment significantly optimized the lost weight and shortened colon, restored the balance of inflammation, mitigated oxidative stress, and restored intestinal epithelial mucosal damage. And, the PCPs exhibited superior efficacy in ameliorating these symptoms compared with PCP-1 and PCP-2. However, depletion of the gut microbiota diminished the therapeutic effects of PCPs in UC mice. Furthermore, fecal transplantation from PCP-treated UC mice to new UC-afflicted mice produced therapeutic effects similar to PCP treatment. So, PCPs significantly ameliorated the symptoms, inflammation, oxidative stress, and intestinal mucosal damage in UC mice, and gut microbiota partially mediated these effects.